Mental health risk, safety, and the lost soul - Buckingham, Christopher; Adams, Ann; Ahmed, Abu (Univerzita Pardubice, 2016)
Introduction: People’s lives depend on mental-health problems being recognised at an early stage so that risks such as suicide and harm to others can be detected and appropriately managed. This was the motivation for the GRiST web-based decision support system. It was developed to bring mental-health expertise into the community so that people can detect risks even if they do not have specialist mental-health training themselves. Methods: The research started in 2002 using a mixture of methods, including interviews, thematic analysis represented by mind maps, focus groups, and action research, all realised within the evolving GRiST software. Results: The GRiST web version was adopted in earnest from 2010. It has now accumulated nearly one million risk assessments from practitioners in specialist mental-health services. The latest research has reached out to people in the community by providing a new self-assessment version, myGRaCE. People can use myGRaCE to help understand their own mental health problems, find out where the main issues and risks reside, and create a comprehensive report that helps them receive appropriate support. Conclusions: The paper describes the development of GRiST and how it has tried to shift the focus from organisations to the individual. Pressure to constrain risk evaluation to include only risk-specific symptoms has been resisted because the prevailing context and long-term causes are all fundamental to detecting and managing risks. The whole person has to be understood: body and soul.
Keywords: decision support; GRiST; mental health; myGRaCE; risk assessment